Entrepreneurial (re)orientation in the face of crisis: Is it worth modifying entrepreneurial strategy? - Marcin Suder (Journal of Entrepreneurship, Management and Innovation)
PURPOSE: This article aims to determine how companies in the SME sector modify their business strategies in response to changes in the external environment. The research focused on modifications to entrepreneurial strategies expressed through the fundamental dimensions of entrepreneurial orientation (EO): risk-taking, innovativeness, and proactiveness. Additionally, it identified which types of reactions (modifications in strategies) lead to the most favorable changes in firm performance. The external environment was determined based on the market situation that resulted from the emergence of the COVID-19 pandemic. METHODOLOGY: This is quantitative research. The study utilized data from 126 small printing businesses operating throughout Poland. Analyses were conducted on the data that reflected modifications in entrepreneurial behaviors and performance during three periods: the pre-crisis period, the initial phase of the crisis (the full lockdown period), and the second phase of the crisis (the period of easing the restrictions). The identification of the behavior types was carried out using cluster analysis. FINDINGS: The results of the research led to the conclusion that, with a change in market conditions, companies significantly change their levels of EO. In particular, the surveyed companies reduced their levels of EO during the outbreak of the COVID-19 pandemic. At the same time, this decrease was mainly due to significant decreases in risk-taking. The levels of EO increased when the conditions improved due to significant increases in innovativeness and proactiveness. Moreover, the analysis enabled the identification of four types of reactions to the emergence of the crisis as well as three types of reactions to the improvement of the external conditions that resulted from the easing of restrictions and the introduction of anti-crisis support measures for businesses. Additionally, it was demonstrated that the type of reaction had a significant impact on the changes in the performances of the examined companies. In particular, it was shown that the lowest decline in performance during the initial phase of crisis could be observed in passive enterprises, i.e., those that did not modify their entrepreneurial strategies (did not alter their levels of individual dimensions of EO). The greatest increase in performance was achieved during the period of easing restrictions by those companies that significantly enhanced their activities across all of the considered dimensions of EO. IMPLICATIONS: The research results provided insights for entrepreneurs in strategic management. Specifically, they learned about the modifications in entrepreneurial behaviors that could lead to the most favorable and optimal improvements in a firm’s performance when market conditions change. ORIGINALITY AND VALUE: The study contributes to the literature concerning reactions to changes in market conditions. This innovative approach considers dynamics where the changes themselves are variables. In particular, this research identifies types of entrepreneurial reactions to market condition changes in terms of dimensions of entrepreneurial orientation. Furthermore, it provides an answer to how firm performance evolved regarding various reaction types (using the example of the printing industry).